Publication trends in The SA Journal of Physiotherapy for the decade 1985-1994 - A. B.W. Dladla; L. Gumede; L. Lin; T. Puckree (AOSIS, 1997)
The primary purpose of this study was to determine trends in the types and first authorship of articles that appeared in the South African Journal of Physiotherapy for the decade, 1985-1994. All 140 articles in the 40 issues of the South African Journal of Physiotherapy for the decade were classified as either research or non-research articles. Research articles using qualitative methodologies were distinguished from those with quantitative ones. First authors of the articles were classified as either physiotherapy academics, physiotherapy students, clinicians or non-physiotherapists. The results show no significant difference in the number of research vs. non-research articles published for the decade. More non-research articles were published in the first five year period while research articles predominated in the second five year period. Quantitative studies using the experimental method appeared significantly more often in the first five years compared to the second five year period. The majority of the papers were first authored by physiotherapists especially academics. Methodologies and first authorship of papers published in the South African Journal of Physiotherapy revealed an interesting trend, thereby providing clues to growth points and deficits within the profession.